2021
DOI: 10.1186/s43043-021-00086-z
|View full text |Cite
|
Sign up to set email alerts
|

Cementing the relationship between conventional and advanced semen parameters

Abstract: Background Affordable conventional semen analysis remains a fundamental procedure to be performed routinely during the diagnosis of male infertility. Advanced semen analyses provide valuable clinical insights in treatment-related decision-making, but these are highly expensive and lack universal standardization. This study aimed at determining the relationship between conventional semen parameters, measured with assistance of computer-aided sperm analysis (CASA), and a set of advanced semen tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…Furthermore, the observed inverse relationship between intracellular sperm O −• 2 levels and VAP is important in advancing our understanding of the possible role of free radicals in constraining the actual rate of sperm-forward movement within the female reproductive tract, which is vital for successful fertilization. These scientific revelations complement those of previous investigators and contribute, additional evidence, with respect to the significance of detailed CASA motility, velocity and kinematic parameters in cementing the relationship between conventional semen analysis and the oxidative status (107).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the observed inverse relationship between intracellular sperm O −• 2 levels and VAP is important in advancing our understanding of the possible role of free radicals in constraining the actual rate of sperm-forward movement within the female reproductive tract, which is vital for successful fertilization. These scientific revelations complement those of previous investigators and contribute, additional evidence, with respect to the significance of detailed CASA motility, velocity and kinematic parameters in cementing the relationship between conventional semen analysis and the oxidative status (107).…”
Section: Discussionsupporting
confidence: 70%
“…In this regard, the SURRG has published the most recent and comprehensive study aiming at establishing statistical correlations between conventional semen parameters obtained with Computer-aided sperm analysis (CASA) and a set of OS and membrane lipid peroxidation variables. The insight gained from this study complement those of previous investigations and contribute additional evidence with respect to the significance of detailed CASA motility, velocity and kinematic parameters in bridging the gap between conventional semen analysis and the oxidative status ( 107 ). Results obtained from this study indicates that rapid progressive motility should prove to be particularly valuable sensitive indicator of lipid peroxidation that could be impaired prior to any detectable deterioration in other sperm motion characteristics.…”
Section: Os-induced Changes In Conventional Semen Parameterssupporting
confidence: 70%
“…This systematic review includes the highest amount of studies to date and finds supporting results when compared with three earlier systematic reviews investigating the influence of EA on semen quality and clinical outcomes following ART [ 12 , 13 , 44 ]. One review from 2021 compared <2, 2–7 and >7 days of EA and found the highest pregnancy and live birth rate with EA of <2 days compared with 2–7 and >7 days.…”
Section: Discussionmentioning
confidence: 68%
“…The sixth edition of the WHO manual for examining and processing human semen has been recently released, recommending 2–7 days of EA prior to semen collection for diagnostic purposes [ 2 ]. Several recent studies have reported a correlation between short EA and lower DNA fragmentation and thus better semen quality [ 12 , 13 ]. Much indicates that a short EA in the context of ART may lead to higher pregnancy rates.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study did not reveal a strong correlation of SC with sperm motility and kinematics, except with the VAP variable, where significant correlation was noticed. VAP is considered as the time-averaged velocity of the sperm head along its average path, indicating the forward speed of a spermatozoon [ 20 ]. It is an important parameter which has been significantly negatively correlated with seminal plasma thiobarbituric acid-reactive substances (TBARS) and intracellular superoxide (O 2 −• ) levels in human sperm [ 21 ].…”
Section: Discussionmentioning
confidence: 99%